Thoracoscopic Stage Internal Traction Repair Reduces Time to Achieve Esophageal Continuity in Long Gap Esophageal Atresia - Borselle, Dominika; Davidson, Joseph; Loukogeorgakis, Stavros; De Coppi, Paolo; Patkowski, Dariusz (European Journal of Pediatric Surgery, 2024)
Objective Management of long gap esophageal atresia (LGOA) is controversial. This study aims at comparing the management of LGOA between two high-volume centers.Methods We included patients with LGOA (type A and B) between 2008 and 2022. Demographics, surgical methods, and outcomes were collected and compared.Results The study population involved 28 patients in center A and 24 patients in center B. A surgical approach was thoracoscopic in center A, only for one patient was open for final procedure. In center B, 3 patients were treated only thoracoscopically, 2 converted to open, and 19 as open surgery. In center A primary esophageal anastomosis concerned 1 case, two-staged esophageal lengthening using external traction 1 patient, and 26 were treated with the multistaged internal traction technique. In 24 patients a full anastomosis was achieved: in 23 patients only the internal traction technique was used, while 1 patient required open Collis–Nissen procedure as final management. In center B primary anastomosis was performed in 7 patients, delayed esophageal anastomosis in 8 patients, esophageal lengthening using external traction in 1 case, and 9 infants required esophageal replacement with gastric tube. Analyzed postoperative complications included: early mortality, 2/28 due to accompanied malformations (center A) and 0/24 (center B); anastomotic leakage, 4/26 (center A) treated conservatively—all patients had a contrast study—and 0/24 (center B), 1 case of pleural effusion, but no routine contrast study; recurrent strictures, 13/26 (center A) and 7/15 (center B); and need for fundoplication, 5/26 (center A) and 2/15 (center B). Age at esophageal continuity was as a median of 31 days in center A and 110 days in center B. Median time between initial procedure and esophageal anastomosis was 11 days in center A and 92 days in center B.Conclusion Thoracoscopic internal traction technique reduces time to achieve esophageal continuity and the need for esophageal substitution while maintaining a similar early complication rate.
Keywords: long gap esophageal atresia; esophageal atresia; internal traction; minimally invasive surgery; delayed primary anastomosis